The Influence of Principal Leadership Style and Teacher Work Motivation on the Performance of Certified Teachers at SMA Negeri Kotamobagu, North Sulawesi, Indonesia - Henny Nikolin Tambingon (Intelektual Pustaka Media Utama, 2018)
The purpose of this study is to analyse and interpret the influence of principal leadership style on the performance of certified teachers, the influence of teacher work motivation on the performance of certified teachers and the influence of principal leadership style and teacher work motivation simultaneously on the performance of certified teachers in SMA Negeri Kotamobagu. This study employs a quantitative study approach with survey methods and multiple regression analysis techniques. The independent variables are principal leadership style (X1) and teacher motivation (X2) and the dependent variable is certified teachers performance (Y). Result of the research shows that the principal leadership style has an effect on the performance of certified teachers, teacher work motivation has an effect on the performance of certified teachers, principal leadership style and teacher work motivation simultaneously affects the performance of certified teachers in SMA Negeri Kotamobagu. The values of the regression coefficients show the influence of each principal leadership style and teacher work motivation on the performance of certified teachers and have a high contribution to the performance of certified teachers. The principal must have the readiness and ability to mobilize the teachers to achieve the goals and be responsible for the organization of educational activities at school. Teachers should be tenacious and skilful at conducting quality learning activities. Schools should have appropriate functions to educational goals and implement effective and efficient organizational management, high social responsiveness, and are sensitive to: teachers, students and the surrounding community.